α‐Lipoic Acid Ameliorates Arsenic‐Induced Lipid Disorders by Promoting Peroxisomal β‐Oxidation and Reducing Lipophagy in Chicken Hepatocyte - Yangfei Zhao; Mingyue Guo; Ting Pei; Chenqi Shang; Yirong Chen; Liying Zhao; Yiguang Lu; Chen Liang; Jundong Wang; Jianhai Zhang (Advanced Science)
Abstract Liver disease poses a significant threat to global public health, with arsenic (As) recognized as a major environmental toxin contributing to liver injury. However, the specific mechanisms and the protective effects of α‐lipoic acid (LA) remain unclear. Therefore, this study employs network toxicology and network pharmacology to comprehensively analyze the hepatotoxic mechanism of As and the hepatoprotective mechanism of LA, and further verifies the mechanisms of peroxisomal β‐oxidation and lipophagy in the process. The network analysis results show that As induces liver damage mainly through autophagy, apoptosis, lipid metabolism, and oxidative stress, whereas LA exerts its hepatoprotective properties mainly by regulating lipid metabolism. Further verifications find that As inhibits SIRT1 expression, activates the P53 and Notch pathways, damages mitochondria, inhibits peroxisomal β‐oxidation, increases lipid accumulation, and enhances lipophagy in the liver, while LA intervention alleviates As‐induced lipid accumulation and enhances lipophagy by targeting SIRT1, ameliorating mitochondrial damage, enhancing peroxisomal β‐oxidation, thereby alleviating As‐induced liver damage. This study further clarifies the mechanism of As hepatotoxicity and provides a theoretical basis for LA as a potential hepatoprotective agent.